Cryopreservation of Cell Culture Derived from Dorsal Root Ganglia of Neonatal Pigs - Ali, Sabina; Moiseieva, Natalia; Bozhok, Galina (Problems of Cryobiology and Cryomedicine, 2020)
The effect of cryopreservation with various concentrations of dimethyl sulfoxide (DMSO) on morphofunctional properties of the dorsal root ganglia cell culture (DRGCC) was investigated in this research. Cells were obtained from the dorsal root ganglia of neonatal piglets and cultured for 7 days in -MEM with 10% fetal calf serum (FCS). These conditions promote a predominant growth of satellite glial cells (SGCs). The resulting culture was cryopreserved at a rate of 0.5 deg / min to –20°C at stage 1, and at 1 deg / min to -80°C at stage 2, afterwards the samples were immersed into liquid nitrogen. Cryoprotective solutions based on α-MEM, 25% FBS, and DMSO at final concentrations of 5, 7.5, and 10% were used. After warming on day 10 of subculturing, the cell viability, relative monolayer area, and glutamine synthetase expression as a marker of SGCs were evaluated. It has been established that cryopreservation of DRGCC using 7.5% DMSO provided 87.7% of viable cells after warming and 85% relative monolayer area in respect of an intact control. The amount of SGCs was about 95%. The obtained results allow us to recommend the chosen regimen for low temperature storage of cell cultures enriched with MG. Probl Cryobiol Cryomed 2020; 30(2): 158–168 </p